From norm to form contemporary urbanism and the materialization of the city - Queiroz Barbosa, Eliana Rosa de (Premio Internacional de tesis de investigación 2017. Transformación urbana. Densidad habitacional y ciudad compacta, 2016)
This work began in august 2012, with the contemporary discussion on Urban Projects and the critical evaluation of instruments promoted by the City Statute (2001), as well as its impact on the production and reproduction of the physical space understood as urban form and urban landscape of contemporary Brazilian cities. The thesis departures from an optimist perspective towards this instruments, especially if compared to the urban policies of the past, seeing its potentials that intend to explore. This posture is partially due to the interactions with researchers from other contexts, interested in studying and acknowledging the mechanisms of production and funding of the Brazilian urban space. Observe this intellectual movement searching for Brazilian solutions, especially concerning the Urban Operations, was very important and certainly influenced the choice of theme and goals of this thesis. This work is also inserted in the range of research that aims is to qualify the urban space of Brazilian cities, accomplishing a critical analysis of the outcome of the contemporary urban development, orchestrated by the instruments mentioned above, in a context of economic expansion, questioning the actual role and potential of Urbanism and its instruments in this conjuncture, as the urban project and urban design strategies.